2019
DOI: 10.18261/issn.1891-943x-2019-03-04-03
|View full text |Cite
|
Sign up to set email alerts
|

Illustrating and analysing power andcontrol relations in Finnish one-to-one computing classrooms

Abstract: This paper reports on teacher practices in tablet-based Finnish one-to-one computing classrooms in grades 7-9. The aim of this study was to increase the understanding of teacher practices by illustrating and analysing the relations of power and control in Finnish teachers' one-to-one computing classrooms. The study applied methods based on classroom observations, photographs and audio recordings of the teachers' communication. Within the context of this study, the results indicate two theoretically distinct, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
0
7
0
1
Order By: Relevance
“…Our analysis is achieved by revisiting data from three Nordic studies on one-to-one computing classrooms. The studies from which we derive data represent Denmark (Meyer, 2020), Finland (Bergström, 2019) and Sweden (Bergström & Mårell-Olsson, 2018;Bergström et al, 2019). These include 67 classroom observations in total and explore teaching practices in which all teachers and students had a personal tablet (Burden et al, 2012).…”
Section: Methodology: Revisiting Ethnographic Data From Three Prior Smentioning
confidence: 99%
See 3 more Smart Citations
“…Our analysis is achieved by revisiting data from three Nordic studies on one-to-one computing classrooms. The studies from which we derive data represent Denmark (Meyer, 2020), Finland (Bergström, 2019) and Sweden (Bergström & Mårell-Olsson, 2018;Bergström et al, 2019). These include 67 classroom observations in total and explore teaching practices in which all teachers and students had a personal tablet (Burden et al, 2012).…”
Section: Methodology: Revisiting Ethnographic Data From Three Prior Smentioning
confidence: 99%
“…The digitalisation of K-12 education has grown rapidly worldwide through one-to-one computing initiatives based on the principle of one laptop or tablet for each student (Islam & Grönlund, 2016). In the Nordic countries, studies on teachers' practice in oneto-one computing classrooms have been reported in Sweden (Fleischer, 2013;Håkansson Lindqvist, 2015;Tallvid, 2015), in Norway (Blikstad-Balas, 2012; Blikstadt-Balas & Klette, 2020), in Denmark (Jahnke, Norqvist, & Olsson, 2014;Meyer, 2015) and in Finland (Bergström, 2019). Although one-to-one computing has become widespread in schooling, research is still needed to understand the complexities of significant and specific changes in teachers' practices and how they affect learning (Burnett, Merchant, Simpson, & Walsch, 2017).…”
Section: Prior Studies On One-to-one Computing Classroomsmentioning
confidence: 99%
See 2 more Smart Citations
“…Klassrummen har för eleverna blivit allt mer personligt formade och fungerar sålunda i allt mindre grad som gemensamma interaktionella utrymmen (Paakkari, 2020;Sahlström et al, 2019a;Sahlström et al, 2019b). Lärarna behöver förhålla sig till nya villkor relaterade till kontroll och distribuerad makt i klassrum där de digitala resurserna erbjuder och utmanar de mer traditionella praktikerna (Bergström 2019;Bergström et al,2019). Än så länge tar det logistiska och tekniska stort utrymme i klassrummen och utifrån den forskning som redovisas ovan förefaller inte undervisningens struktur och innehåll ha genomgått särskilt kraftiga förändringar, men däremot förstärker en allt högre grad av individualisering av skola och utbildning.…”
Section: Digitaliserad Skola -Förändrad Undervisning?unclassified